Inactivation of PPARβ/δ adversely affects satellite cells and reduces postnatal myogenesis - Chandrashekar, Preeti (2016)
Peroxisome proliferator-activated receptor β/δ (PPARβ/δ) is a ubiquitously expressed gene with higher levels observed in skeletal muscle. Recently, our laboratory showed (Bonala S, Lokireddy S, Arigela H, Teng S, Wahli W, Sharma M, McFarlane C, Kambadur R. J Biol Chem 287: 12935–12951, 2012) that PPARβ/δ modulates myostatin activity to induce myogenesis in skeletal muscle. In the present study, we show that PPARβ/δ-null mice display reduced body weight, skeletal muscle weight, and myofiber atrophy during postnatal development. In addition, a significant reduction in satellite cell number was observed in PPARβ/δ-null mice, suggesting a role for PPARβ/δ in muscle regeneration. To investigate this, tibialis anterior muscles were injured with notexin, and muscle regeneration was monitored on days 3, 5, 7, and 28 postinjury. Immunohistochemical analysis revealed an increased inflammatory response and reduced myoblast proliferation in regenerating muscle from PPARβ/δ-null mice. Histological analysis confirmed that the regenerated muscle fibers of PPARβ/δ-null mice maintained an atrophy phenotype with reduced numbers of centrally placed nuclei. Even though satellite cell numbers were reduced before injury, satellite cell self-renewal was found to be unaffected in PPARβ/δ-null mice after regeneration. Previously, our laboratory had showed (Bonala S, Lokireddy S, Arigela H, Teng S, Wahli W, Sharma M, McFarlane C, Kambadur R. J Biol Chem 287: 12935–12951, 2012) that inactivation of PPARβ/δ increases myostatin signaling and inhibits myogenesis. Our results here indeed confirm that inactivation of myostatin signaling rescues the atrophy phenotype and improves muscle fiber cross-sectional area in both uninjured and regenerated tibialis anterior muscle from PPARβ/δ-null mice. Taken together, these data suggest that absence of PPARβ/δ leads to loss of satellite cells, impaired skeletal muscle regeneration, and postnatal myogenesis. Furthermore, our results also demonstrate that functional antagonism of myostatin has utility in rescuing these effects.